Superiorly based pharyngeal flap versus myomucosal resection and direct closure of the posterior pharyngeal wall (Mahrous technique) for surgical correction of velopharyngeal insufficiency - Ahmed Mahrous Mohamed; Zeinab Khalaf; Wafaa Helmy Abd El Hakeem; Doaa Mousa (Wolters Kluwer Medknow Publications, 2024)
Introduction: Superiorly based pharyngeal flap is one of the most common surgical techniques described for surgical correction of velopharyngeal disorders. Being a technique-sensitive and owing to its associated complications, a simple technique has been introduced and compared with it. Aim: The aim was to compare the surgical results and the phoniatric outcome of the superiorly based pharyngeal flap versus the myomucosal resection and direct closure of the posterior pharyngeal wall. Patients and Method: One hundred patients of both sexes were classified into two groups. Group A patients included fifty patients who had velopharyngeal insufficiency (VPI) and were surgically corrected by the superiorly based pharyngeal flap. Group B patients included fifty patients who had VPI and were surgically corrected by myomucosal resection and direct closure of the posterior pharyngeal wall. Results: Postoperatively, 13% of Group A patients had open nasality Grade 4 as compared to 0% in Group B patients. Hyponasality and obstructive sleep apnea were not recorded in any case of Group B patients as compared with 10% of Group A patients. With regard to the postoperative velopharyngeal gap during speech, 18% of patients in Group A had velopharyngeal gap 3 mm, while 10% of patients in Group B had velopharyngeal gap 3 mm. Conclusion: Myomucosal resection and direct closure of the posterior pharyngeal wall is a simple reliable technique for the correction of velopharyngeal disorders.